Repatriation, rehabilitation, and reintegration: the need for a unified policy approach - Noor Huda Ismail (2024)
Southeast Asian policymakers must adopt a nuanced and comprehensive approach in dealing with the repatriation of their citizens affiliated with terrorism. This approach calls for policies that recognise the individual needs of the returnees, ensures their rehabilitation and fosters their reintegration into society. This analysis, which is based on case studies in Indonesia, emphasises the imperative for united action, and urges policymakers to craft comprehensive responses that enhance the prospects for rehabilitation and reintegration.